Comparing Observed Properties of Winds in Low-luminosity Active Galactic Nuclei with Theoretical Predictions - Fangzheng Shi; Feng Yuan; Francesco Tombesi; Fu-guo Xie (The Astrophysical Journal)
Theoretical and numerical simulations of black hole hot accretion flows have shown the ubiquitous existence of winds and predicted their properties, such as velocity and mass flux. In this paper, we have summarized from the literature the physical properties of winds launched from low-luminosity active galactic nuclei (LLAGN), which are believed to be powered by hot accretion flows, and compared them with theoretical predictions. We infer that for both ultrafast outflows and hot winds, the observed wind velocity as a function of their launching radius and the ratio between wind mass flux and black hole accretion rate show good consistency with theoretical predictions. For the prototype LLAGN M81* with abundant observational data, we have examined various observed properties of wind in detail, including velocity, mass flux of the wind, the power-law index of the radial profile of inflow rate, and the jet-to-wind power ratio. Good agreements are found with theoretical predictions, providing strong support to the theory of wind launched from hot accretion flows.